Pengaruh Faktor Pribadi dan Promosi Terhadap Keputusan Pembelian Alat Kesehatan Medis Pada PT. Suricon Gemilang Karya - Arisanti, Qoidah; Fitriyasari, Anis; Fadhillah, Is (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This study aims to analyze "The Effects of Personal Factors and Promotion on Purchasing Decisions for Medical Devices at PT Suricon Gemilang Karya" In this study, personal and promotional factors are the main focus. Several previous studies have also examined the influence of personal factors and promotions on purchasing decisions for health products. The results of this study are expected to contribute to developing a more effective and efficient marketing strategy for medical devices at PT Suricon Gemilang Karya. Hopefully, this research can provide a more comprehensive insight into the factors that influence purchasing decisions for medical devices. The research method that researchers use is quantitative by taking a population of 100 respondents who are given a questionnaire containing statements in accordance with the variable indicators of personal factors and promotional variables. The conclusion of this study shows that the personal factor variable and the promotion variable have a positive and significant effect on purchasing decisions for medical devices at PT Suricon Gemilang Karya. It has been proven in quantitative tests such as the T-test and F-test and Multiple Linear Regression Analysis.